Beneficial Effects of a Low-Glycemic Diet on Serum Metabolites and Gut Microbiota in Obese Women With Prevotella and Bacteriodes Enterotypes: A Randomized Clinical Trial - Hur, Haeng Jeon; Wu, Xuangao; Yang, Hye Jeong; Kim, Min Jung; Lee, Kyun-Hee; Hong, Moonju; Park, Sunmin; Kim, Myung-Sunny (Frontiers in Nutrition, 2022)
Generalized healthy eating patterns may not benefit everyone due to different genetics and enterotypes. We aimed to compare the effects of a low-glycemic diet representing Korean traditional balanced diet(Low-GID) and Westernized diet as a control diet(CD) on anthropometry, serum metabolites, and fecal bacteria in a randomized clinical trial according to enterotypes. We recruited 52 obese women aged 30-50 years, and they consumed Low-GID and CD meals for 1 month, with a 1-month washout period, in a crossover randomized clinical trial. The Low-GID was mainly composed of whole grains with fish, vegetables, seaweeds, and perilla oil, whereas CD contained refined rice, bread, noodles, meats, and processed foods. Serum lipid profiles, metabolomics, serum short-chain fatty acids, and fecal bacteria were analyzed. The important variables influenced by Low-GID and CD were determined by SHAP value in the XGBoost algorithm according to Bacteroides(ET-B) and Prevotella(ET-P). Low-GID and CD interventions did not change the enterotypes, but they modified serum metabolites and some fecal bacterial species differently according to enterotypes. The 10-fold cross-validation of the XGBoost classifier in the ET-P and ET-B clusters was 0.91±0.04 and 0.8±0.07, respectively. In the ET-P cluster, serum L-homocysteine, glutamate, leucine concentrations, and muscle mass were higher in the CD group than in the Low-GID group, while serum 3-hydroxybutyric acid concentration was significantly higher in the Low-GID group than in the CD group(P<0.05). In fecal bacteria, Gemmiger formicilis, Collinsella aerofaciens, and Escherichia coli were higher in the CD group than in the Low-GID group. In the ET-B cohort, serum tryptophan and total cholesterol concentrations were higher in the CD group than in the Low-GID group, while serum glutathione and 3-hydroxybutyric acid concentrations were significantly higher in the Low-GID group than in the CD group(P<0.05). However, in the ET-B cluster, Bifidobacterium longum was much higher in CD than Low-GID, but serum butyric acid levels were higher in the Low-GID than in the CD group. In conclusion, Low-GID can be recommended to improve lipid profiles and insulin resistance-related amino acids in the circulation in adults with ET-P enterotypes.